Crop Diversification and Crop Disposition in India : An Inter - State Analysis - Kapuria, Cheshta; Kaur, Simrit (Indian Journal of Marketing, 2020)
Given the low productivity and earnings of Indian farmers, especially small and marginal landholders, it is pertinent to understand the constraints under which they operate and correspondingly address the same. Amongst several factors, farmers’ earnings can also improve through crop diversification and conducive crop disposition channels, which involve fewer middlemen. This way, farmers can capture a greater share of value addition in the supply chain from farm-gate to consumer. With this backdrop, the present paper analyzed two specific objectives. First, to estimate the degree of crop diversification and the prominent ways in which crop disposition takes place across states and union territories (UTs) in India, and second, to analyze the relationship between crop diversification and variants of crop disposition in India. Four crop diversification indices were calculated, namely Gibbs and Martin, Herfindal – Hirschman Index, Simpson Diversity Index, and Bhatia’s Index. The paper primarily used GM Index for further analysis. Channels of crop disposition were analyzed through six agencies, that is, local private agents, mandis, input dealers, co-operatives and government agencies, processors, and others. Our findings indicated the following : First, crop diversification remained ‘low’ to ‘moderate’ for most of the Indian states and UTs. Second, though crop diversification increased for several states and UTs during the two Rounds, the pace of improvement was slow. Third, crop disposition is generally undertaken through private agents. Fourth, the relationship between crop diversification and sale to ‘mandis’ was positive and significant, while that between crop diversification and ‘sale to local private agents’ was negative and significant.